Isolation of Circulating Tumor Cells from Multiple Epithelial Cancers with ApoStream(®) for Detecting (or Monitoring) the Expression of Folate Receptor Alpha - O’Shannessy, Daniel J. (Biomark Insights, 2016)
This study describes our efforts to further the field of noninvasive diagnostics, specifically in the area of liquid biopsies in oncology. We employed laser scanning cytometry using highly selective antibodies to interrogate circulating tumor cells (CTCs) that were isolated using ApoStream(®) technology to identify folate receptor alpha (FRα)-positive cells. We demonstrate that FRα(+) CTCs can be isolated from patients with metastatic cancers, including NSCLC adenocarcinoma, breast cancer, and ovarian cancer, whereas squamous cell lung cancer and normal healthy controls were devoid of FRα(+) CTCs. We believe that the developed methodology will have applications in both the diagnosis and the monitoring of FRα-expressing cancers. Folate receptor alpha (FRα) expression may have utility as a potential diagnostic and therapeutic target in solid tumors. As tissue samples are not always available for patient screening, this study evaluated a noninvasive assay in CTCs from blood samples to detect FRα expression. The presence of FRα(+) CTCs enriched using ApoStream(®) and detected using laser capture cytometry was evaluated in blood samples from cancer patients [NSCLC adenocarcinoma (n = 14), breast cancer (n = 20), ovarian cancer (n = 6), and squamous lung cancer patients (n = 6)] and healthy subjects (n = 20). The data demonstrated that FRα(+) CTCs were detected in blood from NSCLC adenocarcinoma, breast, and ovarian cancer patients, whereas squamous cell lung cancer patients and normal healthy controls lacked FRα(+) CTCs as previously known. We demonstrate that CTCs captured using ApoStream(®) can be used to detect FRα(+) CTCs and may have clinical utility as a real-time liquid biopsy for assessing FRα levels in cancer patients.